The human rights perspectives of two human rights organizations: Mazlum-Der and İHD - Akan, Suavi Selim. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
An important part of the increasing debates about the civil society in Turkey has been the human rights issue. The repressive attitudes of Turkish state dominated human rights movements in the pre-1980 period. In the post-1980 era with the impact of large number of prisoners of 1980 military coup and torture and violence against these prisoners, the issues related to human rights challenged Turkish state and its actions more often. Moreover, the failures of Turkey on human rights, and the reports published by several international and national organizations and media have increased the pressure on the national government. After 1980, the Ataturkist, modern, and totalizing identity of the state was also challenged and the expressions of various social and cultural identities by different groups were experienced. These challenges can be classified under two titles: Kurdish nationalism and political Islam. Severe human rights violations were committed by the state on these two opposition movements and as a result of these violations, several civil society organizations were established to protect the rigths of these people. Consequently İHD (Human Rights Association) and Mazlum-Der were established (Association for Human Rights and Solidarity for the Oppressed People), which are mainly descendants of debates related to violations against Kurdish population and political Islam. In the light of these discussions, this study aims to compare the human rights perspectives of these two civil society organizations over cultural relativism and universalism. It also aims to discover the reasons of what motivates these associations when they are shaping their human rights perspectives. While doing this, this study will mainly concentrate on the issues of homosexuality, headscarf and the Kurdish question.
Keywords: Human rights -- Turkey.